Scientific Sovereignty: Canada, the Carnegie Institution and the Earth's Magnetism in the North - Good, Gregory (Scientia Canadensis, 1990)
ABSTRACTIn 1905, magnetic survey work began under the auspices of the Department of Terrestrial Magnetism of the Carnegie Institution of Washington directed by Louis Agricola Bauer. The DTI, wanting world-wide coverage, wished to make observations in Canada but this raised the question of sovereignty. Although the DTI was not a government agency, it was foreign. The impact of its work in Canada was to stimulate geophysical research by the Canadian Meteorological Service and by the Dominion Observatory. This research was undertaken in the context of interdepartmental rivalry which finally resulted in control of the field by the Dominion Observatory.